Biomimetic Self‐Cleaning Anisotropic Solid Slippery Surface with Excellent Stability and Restoration. Issue 7 (12th March 2019) - Guo, Pu; Sun, Yimin; Zhang, Yuqi; Hou, Xueyan; Song, Yanwei; Wang, Ji‐Jiang
Abstract: Anisotropic slippery surfaces are widely used in anti‐fouling, smart control of liquid movement and directional liquid transportation. However, anisotropic slippery liquid‐infused porous surfaces (SLIPS) cannot meet the need of practical applications owing to loss and contamination of liquid lubricants. Inspired by solid epicuticular wax on the surface of land plant leaves, we herein report a type of biomimetic anisotropic solid slippery surface (ASSS) based on paraffin wax‐incorporated paper with directional micro‐grooves. This ASSS material shows anisotropic sliding behavior for liquid droplets with different surface tensions. It is demonstrated to be of excellent stability compared with SLIPS as the solid lubricant cannot be lost and stain the contacting surfaces. It also exhibits outstanding acid and alkali corrosion resistance and restoration capability upon physical damage. Both hydrophilic and hydrophobic contaminants on our ASSS can be self‐cleaned by using only water droplets. Our ASSS extends the fabrication of new slippery materials and overcomes some drawbacks of SLIPS. Abstract : Anisotropic sliding : A novel biomimetic anisotropic solid slippery surface was constructed by using paraffin wax‐incorporated paper with directional micro‐grooves. This material shows excellent anisotropic sliding behavior, stability, corrosion resistance, and self‐cleaning effect for both of hydrophilic and hydrophobic contaminants.